(untitled) (Journal Of Educational and Psychological Researches, 2022)
The study aimed to reveal the obstacles of administrative creativity among the leaders of secondary schools (the curriculum system) in the northern border region, which relate to the obstacles (organizational, motivational, and psychological). In addition, to identify the most important statistical differences between the responses of the members of the study sample, which attribute to the variables (educational qualification, year’s Administrative expertise). To achieve the goal of the study, the researcher used the descriptive analytical approach, and to verify the validity of the tool, it has presented to several referees and faculty members in the educational field. The validity of the internal consistency was also calculated for the phrases and the reliability of the tool was verified using the Alpha Cronbach coefficient S Alpha Cronbach. The questionnaire was applied to the study community consisting of (37) high school leaders for the curriculum system in the northern border region. The results of the study revealed that the general average of obstacles to administrative creativity according to the responses of leaders in secondary schools reached (3.79), with a high degree of appreciation. In addition, there was no statistically significant difference at a level less than (0.05) in any of the obstacles to administrative creativity, individually and collectively, which is attributable to the variable of the academic qualification. Moreover, there were statistically significant differences at a level less than (0.05) in (motivational) obstacles to the variable of years of administrative experience attributable to those with experience of (5-10) years.